An Assessment of Hand Hygiene Practices among Health Care Providers in Operation Theatre - Zara Rizwan, Tooba Mughal, Salman Mohsin, Nasir Ali Rahim Najjad (Pakistan Journal of Medical & Health Sciences, 2023)
Aims: To assess the frequency of hand hygiene opportunities available to health care providers during surgeries and to assess the frequency of hand hygiene practices of health care providers in those hand hygiene opportunities. Study design: Cross sectional study Place and duration of study: Operation theatre and recovery room at The Indus Hospital Korangi Campus and Sheikh Saeed Memorial Campus from 21stMarch 2021 to 30th August 2021 Methodology: Two hundred and eighty one health care professional for 55 surgeries were included for hand hygiene opportunities and their hand hygiene practice. Every opportunity to practice hand hygiene was observed and noted as having occurred (hand wash or hand rub) or missed. Throughout the period, the PI was recorded opportunities for hand hygiene and missed opportunities using WHO’s hand hygiene observational form. Results: The average age of the health care provider was 31.22±8.15 years. The overall adherence to hand hygiene practice according to WHO guidelines was 16.1% while 83.9% were not according to WHO hand hygiene guideline. Failure of hand hygiene practice was significantly high in all type of hand hygiene opportunity. Rate of missed/failure hand hygiene practice was significantly high in nurses and technician and also their qualification (p<0.05). Conclusion: The poor hand hygiene compliance was frequently noticed among health care workers. Hand hygiene should be an educational priority and it needs to be implemented effectively. Therefore, hand hygiene resources is an integral part for better strategic and improvement strategy. Keywords: Hand hygiene, Contamination, Health care associated infections; Prevention.